La Unión Mediterránea (UM) del Presidente Nicolas Sarkozy: ¿la superación del proceso de Barcelona? - Echeverría Jesús, Carlos (UNISCI Discussion Papers, 2007)
In this analysis we want to explore the possibilities offered by the initiative, still French to a great extent, but already approached by Italy and Spain, for building a smaller Euro-Mediterranean space than the current onme, taking into account not only its possibilities but also the obstacles for dialogue and cooperation proposals in the region.
Keywords: France; Mediterranean